INSURANCE OF VARIOUS OF PROJECT FINANCING RISKS - Gulirano Nosirova Abdulaziz kizi (Scholar Express Journals, 2025)
This article discusses project management, which requires a comprehensive approach to solving multiple tasks, one of which is effective risk management. Risks can be caused by both external and internal factors, and their impact on project success can be significant. In this context, risk insurance becomes an important tool for minimizing losses and ensuring successful project implementation
Keywords: project; risk